The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1128/jvi.02327-10
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Chimeric La Crosse Virus Expressing the Surface Glycoproteins of Jamestown Canyon Virus Is Immunogenic and Protective against Challenge with either Parental Virus in Mice or Monkeys

Abstract: La Crosse virus (LACV) and Jamestown Canyon virus (JCV), family

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…In additional studies using an attenuated CSG virus clone, neurovirulence was primarily determined by the L segment, but again the neurovirulence phenotype also appeared dependent on the other genomic segments [180,189]. More recently, a recombinant virus containing the LACV backbone with the M ORF from JCV (rLACV/JCV) showed that the chimeric virus was highly attenuated and unable to cause disease after either IP or IC inoculation at high doses, a surprising result considering both parental LACV and JCV viruses were highly neurovirulent [190]. Taken together, the results of these studies suggest that interactions between multiple CSG viral proteins encoded from multiple genomic segments determine CSG virus virulence.…”
Section: Neuropathogenesis – Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In additional studies using an attenuated CSG virus clone, neurovirulence was primarily determined by the L segment, but again the neurovirulence phenotype also appeared dependent on the other genomic segments [180,189]. More recently, a recombinant virus containing the LACV backbone with the M ORF from JCV (rLACV/JCV) showed that the chimeric virus was highly attenuated and unable to cause disease after either IP or IC inoculation at high doses, a surprising result considering both parental LACV and JCV viruses were highly neurovirulent [190]. Taken together, the results of these studies suggest that interactions between multiple CSG viral proteins encoded from multiple genomic segments determine CSG virus virulence.…”
Section: Neuropathogenesis – Molecular Mechanismsmentioning
confidence: 99%
“…Individual CSG virus proteins may have unexpected phenotypes when expressed outside of their specific genetic context. This may be an advantageous feature in terms of vaccine development, as the highly attenuated rLACV/JCV virus was highly immunogenic and when mice and monkeys were immunized with it, they were protected from subsequent LACV, TAHV, and JCV challenge [190]. However, if reassortants between the CSG viruses can have unique phenotypes from either parental virus, it is possible that more virulent novel reassortants may arise.…”
Section: Neuropathogenesis – Molecular Mechanismsmentioning
confidence: 99%
“…Currently, there is no vaccine available to inhibit LACV infection [4, 5] or therapy to treat virus-induced encephalitis [2]. Thus, a better understanding of the mediators of viral pathogenesis in the central nervous system (CNS) as well as the mechanisms by which adults are protected from the development of encephalitis is necessary to mitigate disease impact.…”
Section: Introductionmentioning
confidence: 99%
“…Ochlerotatus communis is a vector of Jamestown Canyon virus (JCV) and snow shoe hare virus (SSHV) in North America (McLean et al 1981; Heard et al 1990), but the clinical significance of O. churchillensis has not yet been studied. Both viruses are widely distributed across temperate areas of North America, and several boreal Aedes Meigen, 1818 and Ochlerotatus Lynch Arribálzaga, 1891 species are the primary vectors (Grimstad 1988; Andreadis et al 2008; Bennett et al 2012). Although JCV antibodies have been detected in moose, elk, bison, mule deer, domestic bovine and equine, white-tailed deer is the only known amplifying host in the natural transmission cycle of the virus (Grimstad 1988; Rust et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…SSHV was isolated for the first time from snowshoe hare ( Lepus americanus Erxleben, 1777; Mammalia: Leporidae) in Montana, United States of America in 1959 (Burgdorfer et al 1961). However, its antibodies also have recently been detected in several small vertebrates and domestic animals such as equine, cattle, dog, and chicken (Bennett et al 2012). The symptoms of SSHV infection in humans include fever, headache, vomiting, meningitis, and encephalitis (Fauvel et al 1980).…”
Section: Introductionmentioning
confidence: 99%